Applications of dielectric pads, novel materials and resonators in 1.5T and 3T MRI. (March 2020) - Slobozhanyuk, A.; Zivkovic, I.; Shchelokova, A.; Mikhailovskaya, A.; Sushkov, I.; Nenasheva, E.; Melchakova, I.; Belov, P.; Webb, A.
Abstract: In order to boost the performance of magnetic resonance imaging without increasing the static magnetic field, it is necessary to increase its intrinsic sensitivity. This allows a reduction in the scanning time, increased spatial resolution, and can enable low-field strength systems (which are much cheaper and can be used to scan patients with metallic implants) to have a higher signal-to-noise ratio (SNR) so that they are comparable to more expensive higher field strength systems. In this contribution, we demonstrate radiofrequency field enhancing and shaping devices based on novel materials, such as high permittivity dielectric structures and metamaterials. These materials can substantially enhance SNR, thus potentially increasing image resolution or allowing faster examinations.